Be alive: In this volume, you will not merely study a book - you will meet a person - Wiersbe, Warren W.; (1929-2019) (United Stated of America, 1986)
When Jesus spoke, people listened. When Jesus traveled, people followed. When Jesus arrived, hearts and lives were transformed.
Keywords: Bible -- John -- Commentaries